Planejamento de manutenção no casco e hélice de navios por meio da análise de dados - Santos, Rafael Fischer Dutra e Mello dos (2017)
The global shipping industry is under constant pressure to develop sustainable alternatives related to the emission of greenhouse gases, which is directly related to the fuel consumption. One of the main problems of vessel’s performance is consequence of deterioration of the hull and propeller. Based on this, it is necessary to predict the best maintenance interval without increasing resource spending. The sailing data was analyzed through data mining method, from the pre-processing of the database to the regression and classification analyzes. The result is a model of hull and propeller maintenance planning that identifies the best interval for execution of interventions in order to avoid a significant increase in ship consumption. The study demonstrates that it is possible to improve the efficiency of a fleet by means of this model developed from the sailing data already available in the daily routine of the vessels.